Development and application of a phosphate-dissolving bacteria agent - YE Ming; TAO Tao; CHEN Wu-xi (浙江大学学报. 农业与生命科学版)
Five bacterial strains with strong phosphate-solubilizing ability were mixed fermentation by C53 composite design, and the co-fermentation systems consisted of the strains Bc, Bs, Ap1 were obtained. The optimum inoculation in degradation of insoluble phosphate in soil was developed through orthogonal design, and the best inoculation ratio was Bc 2%, Bs 6%, Ap1 6%. It was a phosphate-dissolving bacteria agent that the three strains were inoculated in the phosphate-dissolving bacteria fermentation medium according to above-mentioned inoculation ratio and cultured at 30℃ and shaking speed 140 r·min-1 for 28 h. Pot experiment results illustrated that the phosphate-solubilizing bacteria had a good advance on the plant height, root length and shoot fresh mass of Chinese cabbage.